Postojnska Jama in Slovenia, the Südbahn and the Visit of John Charles Molteno: Their Influence on the Development of Railways in South Africa - Craven, Stephen A. (Acta Carsologica, 2006)
In November 1871 a successful businessman and politician from South Africa toured Europe with his daughters. They arrived at Postojnska jama by train from Vienna. He wrote to the governor that it would be very desirable that the engineers should visit the Südbahn which crosses a rugged terrain comparable to that of the Cape mountains where technical problems and increased construction costs slowed the advance. The discovery of diamonds inland was eventually responsible for the extension of the railway to Beaufort West and beyond.